An all-solid-state, lightweight, and flexible asymmetric supercapacitor based on cabbage-like ZnCo2O4 and porous VN nanowires electrode materials. Issue 15 (27th March 2017) - Zhao, Jingxin; Li, Chaowei; Zhang, Qichong; Zhang, Jun; Wang, Xiaona; Lin, Ziyin; Wang, Juanjuan; Lv, Weibang; Lu, Conghua; Wong, Ching-ping; Yao, Yagang
Abstract : The assembled all-solid-state, lightweight, and flexible asymmetric supercapacitor device possessed a higher specific capacitance and volume energy density. Abstract : A series of high-performance all-solid-state, lightweight, and flexible asymmetric supercapacitors (ASC) were prepared using cabbage-like ZnCo2 O4 as the positive electrode material, porous VN nanowires as the negative electrode material, and flexible carbon nanotube film (CNTF) as the collector. Excellent electrochemical performance was achieved with an areal capacitance of 789.11 mF cm −2 for the positive electrode and 400 mF cm −2 for the negative electrode. The assembled all-solid-state flexible ASC device possessed a specific capacitance of 196.43 mF cm −2, large voltage window of 1.6 V, and a volume energy density of 64.76 mW h cm −3 . Moreover, the assembled device exhibited good cycling stability with 87.9% initial capacitance retention after 4000 cycles with the coulombic efficiency remaining close to 100%. In addition, the capacitance retention reached 95.7% after 2000 bending cycles, indicating its good flexible and mechanical stability.